Shape-shift contagion in emerging markets equities: evidence from frequency- and time-domain analysis - Owusu Junior, Peterson; Alagidede, Imhotep; Tweneboah, George (Economics and Business Letters, 2020)
We explore interdependence and contagion in the top 9 emerging markets and the US equities using a novel time-varying GLD-based Baruník & Křehlík (2018) (BK18) spillover technique. The GLD accounts for the extreme returns while the BK18 capture the nonlinear, nonstationary, asymmetric, and time-dependent comovements in higher moments. We find dominance of some emerging markets instead of the US in the frequency-dependent spillovers. We also establish shape shift-contagion in emerging markets equities in the short-term. Our results shed new light on the sources of connectedness and contagion through the shape parameters of equity returns.